Effects of Quick Writing Instruction for High School Students With Emotional Disturbances. (September 2013) - Mason, Linda H.; Kubina, Richard M.; Hoover, Theresa
High school students with emotional disturbances (ED) often struggle with classroom writing tasks. In this study, the effectiveness of Self-Regulated Strategy Development (SRSD) instruction for 10 min timed persuasive quick writes with three high school students with ED was investigated. Results indicated improvement in the areas of quality, response parts, and word count. The acceptability of treatment was positive as indicated by student interviews. Implications for SRSD quick writing for high school students with ED are discussed.